Pharmacognostical Phytochemical and Pharmacological Review on Tridax procumbens Linn - Kumar, Shankul (International Journal of Pharmaceutical & Biological Archive, 2012)
Pharmacognostical Phytochemical and Pharmacological Review on Tridax procumbens Linn